PENDIDIKAN MULTIKULTURAL MELALUI INTEGRASI NILAI AKIDAH AKHLAK SEBAGAI STRATEGI PENGUATAN KARAKTER PESERTA DIDIK DI ERA SOCIETY 5.0 - Achmad Fadil; Ayu Wigati; Nur Azizah; Seli Purnama Sari; Nabela Febriani; Nadhila Nur Amrina; Nanda Kasella (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of globalization and technological advancements in the Society 5.0 era have brought significant changes to social, cultural, and educational life, thereby necessitating the strengthening of students’ character. In a multicultural society such as Indonesia, education plays a role not only in developing cognitive abilities but also in instilling moral and social values. This study aims to analyze how multicultural education integrated with moral values can serve as a strategy to strengthen students’ character in the Society 5.0 era. This study employs a qualitative approach using a literature review (library research) design, analyzing various relevant scientific literature such as journal articles, academic books, and previous studies published within the last five years. The findings indicate that the integration of moral values into multicultural education can foster attitudes of tolerance, empathy, social responsibility, and appreciation for diversity among students. Implementation strategies can be carried out through the development of a values-based curriculum, the application of experiential learning, and the utilization of digital technology in the learning process. Thus, the integration of multicultural education and moral values can serve as a crucial approach in developing an adaptive character education model to address the challenges of the Society 5.0 era.